Análise da eficiência da justiça móvel tocantinense - Almeida, Odete Batista Dias (Universidade Federal do Tocantins, 2017)
Based on the premise that the Mobile Traffic Court represents a means of access to justice, combating conflicts in the event of the accident and under certain conditions, we sought to analyze its effectiveness in the present study as well as to find answers that serve as subsidies to legislators, Judges, jurists, scholars and public policymakers to encourage the action of approach of the Judiciary to the citizen, answering the question: Mobile Traffic Justice is an efficacious instrument, effective and efficient in the contingency of demands in the Judiciary, in addition to , mainly, to value human rights through the fast jurisdictional assistance? In order to do so, a quantitative analysis of the data collected in the Court of Justice of the State of Tocantins and the respective Counties with the aforementioned service was carried out, in order to determine the outcome of the Project in a series of agreements, in addition to the possible impact of Mobile Traffic Court in the quantitative indexes of lawsuits filed. It was verified that the work of Tocantins Mobile Traffic Justice needs to be reviewed. It is suggested that their actions be extended to other areas, such as the environmental area and the Special Criminal Courts, which could count on the possibility of using Mobile Justice, for cases of offenses of less offensive potential and that can be transacted. In this case, the movement of people to a criminal hearing would be avoided, in which, most of the time, it causes embarrassment and anxiety to all parties.